1975
DOI: 10.1113/jphysiol.1975.sp011142
|View full text |Cite
|
Sign up to set email alerts
|

The actions of volatile anaesthetics on synaptic transmission in the dentate gyrus.

Abstract: SUMMARY1. The actions of four volatile anaesthetics on the evoked synaptic potentials of in vitro preparations of the hippocampus were examined.2. All four anaesthetics (ether, halothane, methoxyflurane and trichloroethylene) depressed the synaptic transmission between the perforant path and the granule cells at concentrations lower than those required to maintain anaesthesia in intact animals.3. The population excitatory post-synaptic potential (e.p.s.p.) and massed discharge of the cortical cells (population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0
1

Year Published

1976
1976
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(41 citation statements)
references
References 27 publications
(37 reference statements)
4
36
0
1
Order By: Relevance
“…However, the literature is unclear regarding the ability of anesthetics to influence the neurotransmitter release machinery itself. Richards and colleagues found that low concentrations of anesthetics affected chemical transmission but not impulse conduction or cellular electrical properties in hippocampal neurons (Pocock and Richards 1988;Richards 1972;Richards and White 1975). These observations led them to raise the possibility of direct modulation of the release machinery by general anesthetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the literature is unclear regarding the ability of anesthetics to influence the neurotransmitter release machinery itself. Richards and colleagues found that low concentrations of anesthetics affected chemical transmission but not impulse conduction or cellular electrical properties in hippocampal neurons (Pocock and Richards 1988;Richards 1972;Richards and White 1975). These observations led them to raise the possibility of direct modulation of the release machinery by general anesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Richards and colleagues showed that low concentrations of anesthetic affected chemical transmission, but neither impulse conduction nor cellular electrical properties were affected, raising the possibility of direct modulation of the release machinery (Pocock and Richards 1988;Richards 1972;Richards and White 1975). But the significant number of proteins targeted by general anesthetics has made it difficult to isolate the release machinery in many of these experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed electrophysiological analysis of their mode of action has shown that chemical transmission is affected at low anaesthetic concentrations, rather than impulse conduction in the afferent fibres or the electrical properties of the postsynaptic cells (Richards, 1972;Richards & White, 1975;Zorychta et al, 1975). This implies that a significant part of their action involves a disturbance of neurosecretion, a reduction in the sensitivity of the postsynaptic receptors, or both.…”
Section: Introductionmentioning
confidence: 99%
“…Kendig et al, 1979;Bean et al, 1981;Haydon & Urban, 1983a), it has appeared unlikely that interference with the action potential generating system plays an important role in the production of the state of general anaesthesia by anaesthetics at clinical concentrations. Effects of anaesthetic agents are manifest at relatively low concentrations on crayfish stretch receptor firing (Roth, 1980) and on excitability of nerve terminals in the spinal cord (Morris, 1980), but at these sites it is possible that the drugs act by altering transmitter release or transmitter action at synapses, as is apparently the case in hippocampus (Richards & White, 1975), rather than by modifying cell excitability.…”
Section: Introductionmentioning
confidence: 99%